PEMANFAATAN SUMBER DAYA AIR DI DESA UJUNG JAYA TAMAN NASIONAL UJUNG KULON - Ekasari, Emma Yulia; Supriono, Bambang; Satjapradja, Ombo (Jurnal Nusa Sylva, 2012)
The availability of adequate water in the quantity, quality and regularity is very important for the survival of any society, especially in the downstream watershed (DAS). Land conversion in the buffer zone is the beginning of the loss of water through runoff volume that should be conserved for the benefit of society. As intelligent creatures, humans play a major role, with the ability to utilize and manage the nature and its contents for the necessities of life. In harnessing water resources, public anticipate floods and drought early. Active role in conserving water especially in the utilization efficiently and wisely. This study was conducted to determine the potential and utilization of water by local communities to meet the needs of households and the availability of water resources in the future for the community.